Employers’ Perspectives Skills Matrix (EPSM): A Proposed Relationship Skill Matrix - Saleh, Hasan; Abdul Wahab, Nurul Asmida (International Journal of Magistravitae Management, 2024)
The objective of this study is to identify the skills falling short, HEIs’ education system, and graduates’ attributes from the perspectives of employers, highlighting the urgent need for highly skilled employees in Malaysia to support industrial growth and emphasizing the importance of employability skills as an important element for employment in the industrial sector. From this study, a proposed relationship matrix has been developed, designed specifically to serve as comprehensive guideline for literature reviews by the time this study is conducted. The Employers’ Perspectives Skills Matrix (EPSM) was developed based on the employers’ perspectives on skills falling short, HEIs’ education system, and graduates’ attributes. This relationship matrix is anticipated to be a useful tool for current and future researchers to assist them in carrying out similar studies.